Mannose binding lectin and ficolin‐2 polymorphisms are associated with increased risk for bacterial infections in children with B acute lymphoblastic leukemia. Issue 6 (22nd January 2014) - Pana, Zoe Dorothea; Samarah, Fekri; Papi, Rigini; Antachopoulos, Charalampos; Papageorgiou, Theodotis; Farmaki, Evangelia; Hatzipantelis, Emmanuel; Tragiannidis, Athanassios; Vavatsi‐Christaki, Norma; Kyriakidis, Dimitrios; Athanassiadou‐Piperopoulou, Fani; Roilides, Emmanuel
<x xml:space="preserve">Abstract</x> Background We aimed to investigate whether the presence of mannose binding lectin (MBL2), ficolin 2 (FCN2) polymorphisms or the combined deficiency significantly influence the risk and subsequently the frequency of chemotherapy‐induced bacterial infections in children with B acute lymphoblastic leukemia (B‐ALL). Procedure MBL2 polymorphisms for exon 1 and FCN2 polymorphisms for promoter regions −986, −602, −557, −64, −4 and exon 8 regions +6, 359, +6, 424 were determined in children with B‐ALL. FCN2 haplotype was determined by gene sequencing. Number and duration of FN episodes as well as number of bacterial infections were recorded during induction chemotherapy. Results Forty‐four children with B‐ALL (median age 4.3 years, 65.9% males) suffered from 142 FN episodes and 92 bacterial infections (40.2% Gram positive and 59.8% Gram negative). MBL2 low‐risk genotype was found in 59.1%, medium‐risk in 31.8% and high‐risk in 9%. FCN2 low‐risk haplotypes were detected in 38.2%, medium‐risk in 44.1% and high‐risk in 17.6%. MBL2 genotype and FCN2 haplotype were not associated with increased frequency of FN episodes. MBL2 medium/high‐risk genotype and FCN2 medium/high‐risk haplotype were associated with prolonged duration of FN (P = 0.007 and P = 0.001, respectively) and increased number of bacterial infections (P = 0.001 and P = 0.002, respectively). The combined MBL2/FCN2 medium/high‐risk genotype was associated with an increased number of bacterial infections (P = 0.001). Conclusions MBL2 and FCN2 single or combined deficiencies are associated with increased duration of FN episodes as well as increased number of bacterial infections in children with B‐ALL suggesting a prognostic role of these genes. Pediatr Blood Cancer 2014;61:1017–1022. © 2014 Wiley Periodicals, Inc.